Extrapulmonary Tuberculosis (Eptb) : An Overview - Kalam Azad, Khan Abul; Chowdhury, Tasmina (Bangladesh Journal of Medicine, 2022)
Despite extensive research, screening, education, and continuous efforts to try to eradicate and control the infection, tuberculosis is still one of the most prevalent infections throughout the world. Up to 25% of tuberculosis cases present extrapulmonary involvement. and affect mainly children and adults with compromised immune systems. The most common locations are the lymph nodes, pleura and the osteoarticular system. The problem with these types of tuberculosis is the difficulty in establishing a definitive diagnosis, since the clinical symptoms may be vague. It is often necessary to resort to invasive investigation to diagnosis. Treatment for EPTB is with same antitubercular drugs(ATD) regimens for 6 months used for pulmonary tuberculosis (PTB), and any extension of this period is advisable solely in tuberculosis affecting the central nervous system and in Pott’s disease. Besides antibiotics, occasionally, adjuvant therapy with corticosteroid and surgical intervention is recommended. Recent epidemiological studies show a striking increase in DR-EPTB cases ranging from 10–15% across various reports. As a neglected disease, significant developments in rapid and accurate diagnosis and better therapeutic interventions are urgently needed to control the emerging EPTB situation globally. In this review, we discuss the clinical pictures, diagnosis, treatment, and challenges of EPTB. Bangladesh J Medicine 2022; 33: 130-137